Effects of outdoor play on body composition and physical performance in children: the Yamanashi Adjunct study of the Japan Environment and Children’s Study - Masanori Wako; Taro Fujimaki; Jiro Ichikawa; Kensuke Koyama; Ryoji Shinohara; Sanae Otawa; Anna Kobayashi; Sayaka Horiuchi; Megumi Kushima; Zentaro Yamagata; Hirotaka Haro (PLoS ONE, 2025)
Introduction Childhood is a pivotal developmental stage that substantially affects lifelong habits. Recent research has emphasized the vital role of outdoor play in children’s mental and physical well-being. Despite the World Health Organization recommending 1 hour of daily physical activity for children, a knowledge gap exists regarding the specific link between children’s physical performance, body composition (evaluated through bioelectrical impedance analysis [BIA]), and outdoor play habits. Methods Utilizing data from the Japan Environment and Children’s Study, a national birth cohort study, this study included 494 eight-year-old participants. The assessment included body composition (height, weight, body fat percentage, predicted muscle weight, and phase angle using BIA) and physical performance (50 m sprint, standing long jump, 20 m shuttle run, and handgrip strength). Parents provided information on children’s outdoor playtime. Results The group with more outdoor play demonstrated superior sports test results, particularly among boys. Girls engaged in increased outdoor play exhibited higher predicted muscle weights, whereas boys showed greater phase angles in the lower limbs. Handgrip strength correlated with phase angle and predicted muscle weight. Notably, the association between body composition and sports test results was more pronounced in boys than in girls, with phase angles exhibiting stronger links to running and jumping. Conclusion This pioneering study explored the relationship between outdoor play, body composition, and physical performance in children. Outdoor play positively correlated with improved sports performance, revealing sex disparities in body composition changes. Unlike previous studies focusing on general physical development, this study scrutinized specific physical functions, uncovering correlations between phase angle and muscle quality. Findings suggest that outdoor play positively impacts muscle quality, especially in boys, contributing to enhanced physical performance in children. Understanding these effects on body composition and physical activity is imperative for promoting children’s health.